2015
DOI: 10.1039/c4ra16141f
|View full text |Cite
|
Sign up to set email alerts
|

Highly dispersed MnOx nanoparticles supported on three-dimensionally ordered macroporous carbon: a novel nanocomposite for catalytic reduction of NOx with NH3 at low temperature

Abstract: In this paper, we report a novel nanocomposite of MnO x nanoparticles supported by three-dimensionally ordered macroporous carbon (MnO x /3DOMC) fabricated by means of a simple multi-component infiltration of three-dimensional templates and its use as a catalyst for low-temperature selective catalytic reduction (SCR) of NO x with NH 3 . Several techniques, including scanning electron microscopy, X-ray diffraction, N 2 -sorption, transmission electron microscopy, X-ray photoelectron spectroscopy, NH 3 temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…The O 1s spectra obtained on Nb/CeO 2 samples are exhibited in Figure C. The peaks at 529.5–530.0 and 531.7–532.7 eV could be attributed to lattice oxygen O 2– (denoted as O β ) and surface-adsorbed oxygen (denoted as O α ), respectively. , In oxidation reactions, O α , with higher mobility, is more reactive than O β . Therefore, a high O α ratio could favor the oxidation of NO to NO 2 and then contribute to the fast SCR reaction. The relative surface concentration ratios of O α /O all on Nb/CeO 2 catalysts were determined from the corresponding peak areas and are listed in Figure C.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The O 1s spectra obtained on Nb/CeO 2 samples are exhibited in Figure C. The peaks at 529.5–530.0 and 531.7–532.7 eV could be attributed to lattice oxygen O 2– (denoted as O β ) and surface-adsorbed oxygen (denoted as O α ), respectively. , In oxidation reactions, O α , with higher mobility, is more reactive than O β . Therefore, a high O α ratio could favor the oxidation of NO to NO 2 and then contribute to the fast SCR reaction. The relative surface concentration ratios of O α /O all on Nb/CeO 2 catalysts were determined from the corresponding peak areas and are listed in Figure C.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Gao et al reported a novel nanocomposite of MnO x nanoparticles supported on three-dimensionally ordered macroporous carbon (MnO x /3DOMC). They found that this novel catalyst exhibited good water and sulfur tolerance ( Figure 32) [54]. As a special ordered carbon material with unique nanostructure and electronic properties, carbon nanotubes (CNTs) have been reported to be an interesting support for SCR catalysts [98,99].…”
Section: Proper Supportmentioning
confidence: 99%
“…In recent years, catalysts with hierarchical pore structures have attracted much attention for environmental catalytic applications. Due to their adjustable pore sizes and unique structural properties, Gao et al [10] demonstrated manganese oxide nanoparticles with a hierarchical mesopore structure in the walls of the macroporous skeleton supported by three-dimensionally ordered macroporous carbon, which exhibited better low-temperature NH 3 -SCR reaction activity, stability, as well as H 2 O and SO 2 resistance. Fang et al [11] prepared foam-like Fe 2 O 3 @CuO x monolith catalysts with a three-dimensional hierarchical structure and displayed a higher activity, stability, as well as SO 2 and H 2 O resistance than the catalyst without Fe 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%